The Effect of the SrVER Learning Model Assisted by Augmented Reality Media on Biology Learning Outcomes - Muliani, Muliani; Handayani, Baiq Sri; Lestari, Tri Ayu; Setiadi, Dadi (Jurnal Pijar Mipa, 2025)
Effective biology learning requires various components to enhance learning, including implementing appropriate learning models and media. This study examines the effect of the SrVER learning model assisted by augmented reality (AR) media on the biology learning outcomes of 10th-grade students at SMAN 2 Mataram. This research employs a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The study population consists of 13 10th-grade classes at SMAN 2 Mataram, from which four classes were selected as the research sample using purposive sampling. Data was collected through questionnaires and student learning outcome tests. The data analysis techniques used in this study include the N-Gain statistical test and the Mann-Whitney test. The results show that the experimental class achieved an N-Gain score of 0.4 (moderate), while the control class obtained an N-Gain score of 0.2 (low). Furthermore, the Mann-Whitney test yielded an Asymp. Sig (2-tailed) value of 0.001, which is less than 0.05, indicating a significant difference between the post-test scores of the control and experimental classes. These findings confirm that implementing the SrVER learning model assisted by augmented reality media can significantly improve the biology learning outcomes of 10th-grade students.